2022
DOI: 10.1002/pat.5958
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic vulcanizates with an integration of good mechanical performance and excellent resistance to high temperature and oil based on HNBR/TPEE

Abstract: Thermoplastic vulcanizates (TPVs), with a combination of excellent resilience of conventional elastomer and re-processibility of thermoplastic, have been widely explored both in academia and industry in recent years. Herein, a new type of thermoplastic vulcanizates with good mechanical performance, excellent resistance to high temperature and oil has been successfully developed based on hydrogenated acrylonitrile butadiene rubber (HNBR) and thermoplastic polyester elastomer (TPEE) by the masterbatch procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The duration of dynamic vulcanization time is directly related to the cross‐linking time and shear action time of the rubber, therefore the different DV times inevitably have a significant effect on the rubber network strength formed in the TPV system 1 . Previous studies and our recent works have shown that due to the unique “sea‐island” phase structure of TPV composite, the cross‐linked rubber particles can be regarded as fillers dispersed within the continuous thermoplastic matrix 38,39 . Therefore the difference in the rubber network strength formed in TPVs with different DV times can be investigated by RPA strain scanning mode, with the results shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The duration of dynamic vulcanization time is directly related to the cross‐linking time and shear action time of the rubber, therefore the different DV times inevitably have a significant effect on the rubber network strength formed in the TPV system 1 . Previous studies and our recent works have shown that due to the unique “sea‐island” phase structure of TPV composite, the cross‐linked rubber particles can be regarded as fillers dispersed within the continuous thermoplastic matrix 38,39 . Therefore the difference in the rubber network strength formed in TPVs with different DV times can be investigated by RPA strain scanning mode, with the results shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the process for preparing HNBR/TPEE‐TPVs with the HNBR/TPEE mass ratio of 60/40, an optimum composition demonstrated by our previous work 38 . The first step was to thoroughly mix HNBR and DBPH (an effective peroxide cross‐linking agent, the dosage is 1.5 phr with regard to HNBR) in the internal mixer equipped with two counter‐rotating rotors (HAAKE PolyLab OS and Rheomix OS, Thermo Fisher Scientific) at room temperature to obtain the HNBR masterbatch, an optimum procedure 39 .…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations